1977
DOI: 10.1017/s000335610003943x
|View full text |Cite
|
Sign up to set email alerts
|

Rearing of dairy cattle. 7. Effect of level of nutrition and body condition on the fertility of heifers

Abstract: SUMMARYOne-hundred-and-seventy British Friesian heifers were individually fed from 6 weeks before to 6 weeks after artificial insemination on a diet of 90% maize silage and 10% decorticated groundnut in the dry matter. Three levels of nutrition were compared: 48, 55 and 62 g/day of digestible organic matter/kg live weight0·73, which gave mean growth rates of 0·34, 0·50 and 0·68 kg/day respectively. Pregnancy rates to first service were not significantly different, averaging 67, 69 and 65%. Heifers were given a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
3
0
4

Year Published

1979
1979
1992
1992

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 6 publications
7
3
0
4
Order By: Relevance
“…This result is in general accord with conclusions reached by Leaver (1977). This result is in general accord with conclusions reached by Leaver (1977).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This result is in general accord with conclusions reached by Leaver (1977). This result is in general accord with conclusions reached by Leaver (1977).…”
Section: Discussionsupporting
confidence: 92%
“…In experiments in which the design and the heifers involved were essentially similar to those of the present study, Leaver (1977) found that varying the growth rate from 0-34 to 0-68 kg/day did not lead to differences in pregnancy rates determined 8 to 10 weeks after service (AI), these being 0-67 on average. Those few heifers in his experiments that were in poor body condition at AI at the mid-point of the experimental period of 12 weeks did, however, have a lower pregnancy rate (0-42) but the difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…These results are similar to those reported by Leaver (1977), who found no significant relationship between fertility and mean live-weight gains of 0-34, 0-50 and 0-68 kg/day in groups of animals that were fed individually. In trial 1 mean growth rates ranged from 0-39 to 0-93 kg/day in period 1 and from 0 to 0-51 kg/day in period 2.…”
Section: Discussionsupporting
confidence: 91%
“…The liveweight gains were satisfactory for cattle of this type given unsupplemented silages (Waldo, 1977) and the protein intake on the two treatments was in excess of requirements (Roy et al, 1977). The liveweight gains of both groups were within the range associated with normal fertility (Leaver, 1977) and would not be expected to account for differences in conception pattern.…”
Section: Discussionmentioning
confidence: 76%